AB1050 CLINICAL IMPLICATIONS OF ULTRASONOGRAPHY (US) IN DIAGNOSIS AND MONITORING DISEASE ACTIVITY OF RELAPSING POLYCHONDRITIS (RP) AND COMPARATIVE INVESTIGATION BY US BETWEEN AURICLE OF RP, REPEATED TRAUMA, CELLULITIS AND HEALTHY SUBJECT. (2nd June 2020) - Nishikawa, H.; Taniguchi, Y.; Ogasawara, M.; Inotani, S.; Amano, E.; Matsumoto, T.; Hamada-Ode, K.; Shimamura, Y.; Horino, T.; Fujimoto, S.; Terada, Y.
Abstract : Objectives: To assess the clinical implications of ultrasonography (US) in monitoring disease activity and diagnosis of relapsing polychondritis (RP). Methods: Firstly, auricular (n=5) and nasal (n=1) chondritis of six patients with RP were assessed by US before and after treatments. The relationship between US findings and serum markers were evaluated. Moreover, the comparisons of US findings between the auricle of patients with RP (n=5), repeated trauma (n=5), cellulitis (n=2) and healthy subjects (n=5) were also assessed. Results: US finding before treatment showed low-echoic swollen auricular and nasal cartilage with increased power Doppler signals (PDS) in all cases of RP. US findings corresponded to biopsy findings. After treatment, the swollen ear and nose completely resolved. Then, US findings also showed dramatic reductions in swollen cartilage with the decrease in PDS. Although serum markers completely improved, US finding remained in 1 of 6 cases, and this case showed flare due to PSL tapering. Finally, RP could be differentiated from the damage of repeated trauma and cellulitis by the presence or absence of PDS and subperichondrial serous effusion. Conclusion: US of auricular and nasal cartilage in RP possibly facilitates evaluation of auricular lesions and monitoring of disease activity, especially when we consider the treatment response and the timing of drug tapering. Disclosure of Interests: None declared